COVID-19 lockdown compliance, financial stress, and acceleration in technology adoption in rural Uganda - Jana Samira Hamdan; Yuanwei Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We examine the medium-term impact of COVID-19 for financial well-being and technology adoption in a low-income country. The analysis is based on regionally representative panel data consisting of 1,975 micro-entrepreneurs from rural Uganda. Using a LASSO approach, we first show that several business characteristics predict longer business shutdown due to COVID-19, including running a service business. We also find several respondent characteristics correlate with non-compliance to the lockdown, the strongest predictors being independence of mobility restrictions, financial pressure and extreme remoteness. Second, comparing pre- and post-lockdown levels, we document a sharp increase in the use of financial services. Moreover, we find a substantial drop in business investments and profits. Third, we adopt an instrumental variable approach to analyze the causal impact of the COVID-19 business shutdown. We find that businesses which closed longer are more likely to adopt mobile money services and better business practices.
Keywords: I18; I31; O12; 330; COVID-19; Lockdown; Micro-entreprises; Mobile Money; Coping Strategies; Uganda